2019
DOI: 10.3389/fneur.2019.00759
|View full text |Cite
|
Sign up to set email alerts
|

Topological Disruption of Structural Brain Networks in Patients With Cognitive Impairment Following Cerebellar Infarction

Abstract: Cerebellar lesions can lead to a series of cognitive and emotional disorders by influencing cerebral activity via cerebro-cerebellar loops. To explore changes in cognitive function and structural brain networks in patients with posterior cerebellar infarction, we conducted the current study using diffusion-weighted MRI (32 cerebellar infarction patients, 29 controls). Moreover, a series of neuropsychological tests were used to assess the subject's cognitive performance. We found cognitive impairment following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…In recent years, the role of the cerebellum in cognition has been gradually studied, especially in the collaborative management of cognitive functions within the brain. Posterior lobe lesions lead to cerebellar cognitive affective syndrome (CCAS), the typical characteristics of which involve deficits in executive function, linguistic learning, visual spatial processing, and regulation of affect (Wang et al, 2019). Previous studies demonstrate that the underlying mechanisms of cognitive impairment with cerebellar lesions might include abnormal fiber connections observed between the cerebellum and the functional areas of the cerebrum, particularly in the precuneus, cingulate gyrus, and frontal and temporal lobes (Schmahmann, 2019).…”
Section: Interactive Neural Networkmentioning
confidence: 99%
“…In recent years, the role of the cerebellum in cognition has been gradually studied, especially in the collaborative management of cognitive functions within the brain. Posterior lobe lesions lead to cerebellar cognitive affective syndrome (CCAS), the typical characteristics of which involve deficits in executive function, linguistic learning, visual spatial processing, and regulation of affect (Wang et al, 2019). Previous studies demonstrate that the underlying mechanisms of cognitive impairment with cerebellar lesions might include abnormal fiber connections observed between the cerebellum and the functional areas of the cerebrum, particularly in the precuneus, cingulate gyrus, and frontal and temporal lobes (Schmahmann, 2019).…”
Section: Interactive Neural Networkmentioning
confidence: 99%
“…Recent studies have implicated the role of cerebellum in cognitive processes (15)(16)(17)(18)(19). Cerebellar cognitive affective syndrome (CCAS) is characterized by executive dysfunction, spatial cognitive impairment, language deficits, and personality changes (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum could form extensive neural circuits between the cerebrum and cerebellum to modulate cognitive function. Wang et al (2019) showed that cognitive impairment after cerebellar stroke might be related to interrupted brain network. Besides, the connections of neurons in ORB were able to integrate some signals from the external world and internal states to output the thalamus and prefrontal cortex, ongoing cognitive processing ( Rudebeck and Rich, 2018 ).…”
Section: Discussionmentioning
confidence: 99%